Pengaruh Citicoline terhadap Tingkat Keparahan dan Status Fungsional Pasien Stroke Iskemik: Laporan Kasus Berbasis Bukti - Yosefin Joenadi; Dedi Joenadi (Cermin Dunia Kedokteran, 2024)
Background: Stroke is a cause of long-term mortality, morbidity, and disability. Neuroprotectors, such as citicoline, are a choice for patients not eligible for rTPA. This evidence-based case report aims to look at the association of citicoline with the severity and functional status of ischemic stroke. Method: The search is based on the database Scopus. A total of 191 studies were reviewed, and 3 articles were chosen for critical review: Ghosh, et al, (2015), Martynov, et al, (2013), and Mehta, et al, (2019). Results: Significant differences in functional status measured by the Barthel index and modified Rankin Scale (mRS) and severity measured by the NIHSS. Conclusion: Citicoline has a significant effect on the functional status and severity of an ischemic stroke.